Jacobin Cuckoo parasitising African Red-eyed Bulbul nest - de Swardt, Dawid H (Biodiversity Observations, 2010)
... While atlasing the next pentad along the river, the wind became stronger and it turned cold. I went back in my tracks to revisit the nest to confirm the identification of the species. It was about 09:30. On arrival at the nest site, an African Red-eyed Bulbul Pycnonotus nigricans was flushed from the nest. I found a third white egg in the nest.